The role of men in antenatal care and preventing HIV transmission from mothers to infants in Gambella region, Ethiopia. - Mirgissa Kaba; Michelle R Kaufman; Andrea Ruff (Public Library of Science (PLoS), 2022)
Prevention of vertical transmission of HIV has evolved over the past two decades. Although public health agencies advocate for male involvement in such interventions, their role in the prevention of vertical transmission of HIV remains limited. This study aims to explore the role of men in antenatal care and prevention of vertical transmission of HIV in the Gambella region of Ethiopia. The study was conducted among the Nuer and Anuak communities in Gambella region. Participants included female antenatal care attendees at two health centers, men who were husbands, local health extension workers of the catchment villages, and health care providers and managers. Data were collected using focus group discussions, in-depth interviews, and key informant interviews. Recordings were transcribed, coded, and analysed using thematic approaches. MAXQDA version 11 was used to facilitate data organization and reduction. Findings showed that men in Gambella are not expected to accompany their wives to health facilities or encourage them to visit the facilities in connection to pregnancy. Participants reported that men rarely visit health facilities with their partners, and they are largely unaware of the connection between antenatal care during pregnancy and prevention of mother to child transmission of HIV. Participants indicated that women's attendance at health facilities during pregnancy is not a common practice, and if they do visit them in connection to pregnancy there may be suspicion she has HIV. In this cultural context, men do not have a role in the health care of their wives during pregnancy. Men's engagement may be further lessened by the common perception that visiting a health facility in connection to pregnancy is associated with HIV.